Farmers’ Knowledge on Insect Pests of Citrus (Citrus reticulata) and their Management in Gulmi District of Nepal - Chhetri, S.; Bhatta, S.; Kafle, N.; Dahal, B.; Subedi, P. S. (Journal of Agriculture and Environment, 2021)
A study was carried out to assess farmers’ knowledge on insect pests of citrus and Integrated Pest management in citrus zone, Gulmi district. Survey sample size of 105 was taken from Dhurkot Rural Municipality, Chatrakot Rural Municipality and Resunga Municipality of the Gulmi district. Respondents were selected using simple random sampling technique and interviewed. The primary data were collected using pretested questionnaire. The knowledge on citrus insect pest is significantly associated positively with total citrus cultivation area (p=0.1%). The average years of engagement of 23.3 years and average mandarin cultivation area of 0.35 ha gives insight to great potentiality of farmers adopting integrated pest management. The result shows insect’s severity as one of the major problems with major insect pest of citrus as fruitfly, green stink bugs, white grubs, leaf miner, aphid and rent ants. Although (74.3 %) of the total respondents were found to have knowledge about term “IPM technology”, only (35.2%) practiced IPM practices till date. The positive attitude and perception of citrus growers towards IPM technology in the study area depicts great scope for profitable citrus production on a sustainable basis.